2010
DOI: 10.1111/j.1365-2982.2010.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Tonic inhibition of human small intestinal motility by nitric oxide in children but not in adults

Abstract: Background Gastrointestinal motility is dependent on neural influences that largely involve the enteric nervous system (ENS). The main motor patterns that occur in the fasted and fed state are noticeably different in children compared with adults. Although the development of the ENS continues after birth, there is no data on the contractile activity of segments of small intestine from young children. This study was designed to provide data on the development of muscle control by the human ENS with particular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Nitric oxide is the primary neurotransmitter of inhibitory motoneurons in ENS 53 and exerts tonic inhibition on intestinal motility in child 54 . In this study, we found that both TTX and l ‐NAME excited CM contraction.…”
Section: Discussionsupporting
confidence: 50%
“…Nitric oxide is the primary neurotransmitter of inhibitory motoneurons in ENS 53 and exerts tonic inhibition on intestinal motility in child 54 . In this study, we found that both TTX and l ‐NAME excited CM contraction.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies of guinea‐pig, rat and human have reported postnatal changes in the proportions of different types of enteric neurons and in enteric neuromuscular transmission (de Vries et al 2010; Patel et al 2010; Wittmeyer et al 2010). Our study, which is the first to examine developmental changes in electrophysiological and morphological properties of neurons in an intact ENS, found that the main neuron types (DII and S‐neurons with a single long process) comprising reflex pathways underlying the propulsive behaviour of the gut could be distinguished by P0.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in rat neonates, the proportion of nitrergic myenteric neurons increases early in the postnatal life followed by a significant increase in the proportion of cholinergic neurons (44). In the human and guinea pig small intestine, a stronger nitrergic inhibitory component of the neuromuscular transmission is observed in neonates than in adults (32,46). The maturation of the cholinergic phenotype of myenteric neurons is correlated with the development of colonic migrating motor complexes in mice (37) and colonic propulsive motility in rats (44).…”
mentioning
confidence: 94%